Federalism, citizenship, and Quebec : debating multinationalism - Gagnon, Alain (University of Toronto Press, 2007)
"In Federalism, Citizenship, and Quebec, Alain-G. Gagnon and Raffaele Iacovino argue that multinationalism has been and continues to be the fundamental sociopolitical characteristic of the Canadian polity, and that it should guide and structure the negotiating principles and political processes upon which the institutions of federalism and citizenship are constructed."--Jacket